Um estudo enunciativo da metáfora em textos publicitários - Rocha, Aline Wieczikovski (2010)
The study presented here aims to demonstrate how the construction of the metaphor‟s meaning occurs in advertising texts. From Émile Benveniste reflections about the Enunciation Theory, the metaphor is analyzed as an organizing element of the meaning of the text where it is inserted. In this case, the metaphor plays an important role in the textual architecture and in the fulfilment of the functions the advertising text has. This is an important observation, because if so considered, the metaphor can no longer be seen as a merely ornamental language resource. The analysis, supported on the enunciative foundation, observes the metaphor as a linguistic occurrence wich has a double articulation: the language as a system of signs and the language as communication, ie the language that is form and language that is speech. In order to understand the corpus of this work ─ the advertising text ─ it was essential the presence of Bakhtin‟s study on the genres of discourse, because on it a reflective basis is expressed, as well enunciative, where the enunciation is understood as the minimum unit of the discursive communication, and its production and operation, in social practice, create the sense of the speech. Consonant to the bakhtin‟s expression on the discursive genres, it‟s exposed the Marcuschi‟s work on the textual genres, thus substantiating the functions the advertising text exercises before the society. Some characteristics of this genre are distinguished from the position of scholars on the advertising text, whereas image plays a collaborative role in the construction of the senses. From the enunciative analysis of the metaphors, it was observed that the metaphorical sense exists only in the enunciative scene determined by the announcer, ie by the one position he assumes before the listener in each enunciation, in each speech